Evaluation of sexual attitude and sexual function in menopausal age; a population based cross-sectional study - Somayeh Hashemi; Fahimeh Ramezani Tehrani; Masumeh Simbar; Mehrandokht Abedini; Hamid Bahreinian; Roya Gholami (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2013)
Background: Menopause and its physical, hormonal and psychosocial changes could affect women's sexual function. There are controversial results regarding relationship between sexual attitudes and function. Objective: We aimed to evaluate sexual attitudes and sexual function among Iranian menopausal age women. Materials and Methods: This population based cross-sectional study was carried out on 225 menopausal women, aged 45-65 years. Based on a self-made questionnaire data were collected about women's socio-demographic characteristics, attitudes regarding sexuality and sexual function. Data were analyzed using SPSS and sexual function was compared between three groups of women who had positive, medium and negative attitudes regarding sexuality. Results: The mean age of women was 53.11±4.56 years. Seventy percent of them had at least one sexual problem. Feeling of dyspareunia was significantly different between three categories of attitudes regarding sexuality (p=0.03). Comparing data obtained on their attitudes, sexual desire, orgasm and dyspareunia demonstrated significant differences (p=0.03, 0.04, and 0.04 respectively). Conclusion: Attitude regarding sexual function has a great impact on sexual activity of postmenopausal women that need to be considered in their health care programming.